(untitled) (Research, Society and Development, 2021)
Introduction: The Post-Cardiac Arrest Syndrome (PCAS) is characterized by systemic inflammation, followed by risk of multiple organ failure, due to oxidative stress generated after the period of ischemia. Nursing in the clinical management of PPS acts directly in the early identification and conducts that result in reduced risk circumstances. Objective: To identify, through literature, the role of intensivist nursing in the clinical signs of PPSC. Methodology: Integrative literature review. Articles were searched using the Biblioteca Virtual de Saúde (BVS), Base de Dados de Enfermagem (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Review and Online Recovery System (MEDLINE). Results and Discussion: ICU nursing, when facing PCAS, acts by means of interventions aiming at the stabilization of this clinical picture. Thus, continuing education is a relevant tool in the quality of this care, because it is necessary the knowledge about the pathophysiological process and the appropriate assistance. Conclusion: The nursing performance in PCAS and the skill in its management are limited by the lack of standardization and the establishment of specific scores for this disease, and the inadequate dimensioning of the team contributes to worsening the patient’s prognosis, because good care is based on the triad predictability-assistance-team.